The pragmatic-communicative parameters of the functioning of the verbal periphrasis (on the material of the modern Italian language) - Червона, Оксана Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
This article is devoted to the study of the pragmatic-communicative parameters of the functioning of the verbal periphrasis on the material of the modern Italian language. Were reviewed the theoretical foundations of the study of the theory of speech acts and analyzed the classifications of the speech acts according to the use of the verbal periphrasis, and the typology of the study of speech act. Were analysed communicative-pragmatic and affective-evaluative parameters of verbal periphrases of Italian that function in composition SА as an index of intensification of perlocutionary effect and elocutionary force of SА as most recurrent and specific means of language expression.